PENGUATAN NILAI SOPAN SANTUN MELALUI PEMBELAJARAN PPKN DI TENGAH KRISIS ETIKA REMAJA DI ERA DIGITAL DI SMP NEGERI 1 TARUTUNG - Novi Yanti Lumbantobing, Joy; Habeahan, Sampitmo; Halking; Siagian, Liber; Anastasya Sihaloho, Oksari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the condition of students' politeness values and to describe the strengthening of these values through Pancasila Education learning at SMP Negeri 1 Tarutung in the digital era. This study employed a descriptive qualitative method, with the Pancasila Education teacher and students of class VIII- 3 as the research subjects. Data were collected through observation, interviews, and documentation and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that students had demonstrated polite behavior in terms of dress, attitude, and language. However, the implementation of these values had not been fully consistent due to the influence of social media and digital interactions. The strengthening of politeness values was carried out through the habituation of polite behavior, teacher role modeling, the integration of politeness values into learning activities, as well as constructive advice and reprimands. This study concludes that Pancasila Education plays an important role in strengthening students' politeness values, although support from families and communities remains necessary for optimal character development. Keywords: Politeness, Pancasila Education, Adolescent Ethics in the Digital Era